A taxonomic reassessment of the Vittiaceae (Hypnales, Bryopsida): Evidence from phylogenetic analyses of combined chloroplast and nuclear sequence data - Vanderpoorten, A. (2014)
The Vittiaceae are a small family of aquatic mosses that are defined based on gametophytic traits whose interpretation has led to conflicting taxonomic arrangements. Phylogenetic analyses of two cpDNA regions, trnL-trnF and atpB-rbcL, indicate that Vittia is nested within the Amblystegiaceae s. str., suggesting that the family Vittiaceae should not be recognized. Platylomella lescurii appears nested within the Thuidiaceae/Leskeaceae. This suggests that the series of character states shared by Vittia and Platylomella, including a differentiated leaf border, short laminal cells, stiff stems, and a thick costa, are convergent features that arose independently in unrelated lineages of aquatic Hypnales. Within the Amblystegiaceae, phylogenetic analyses of the two cpDNA regions combined with ITS sequence data show that Hypnobartlettia, Vittia elimbata spec. nov., V. pachyloma, and V. salina, despite their strong morphological similarity to aquatic Amblystegium species, form a clade that is sister to the Drepanocladus/Pseudocalliergon complex. This combined clade is unresolved at a polytomy that includes Amblystegium serpens and a clade including all the other Amblystegium species. The occurrence of A. serpens outside the strongly supported clade including other Amblystegium species suggests that A. serpens may be better accommodated in a distinct genus. Amblystegium serpens is the type species of Amblystegium and thus retains the name. The other species are accommodated in their own genus, Hygroamblystegium, including H. fluviatile, H. humile comb. nov., H. noterophyllum, H. tenax, and H. varium.